Occurrence of ABO And RhD Incompatibility with Rh Negative Mothers - Izetbegovic, Sebija (AVICENA, d.o.o., Sarajevo, 2013)
INTRODUCTION: Hemolytic disease of the newborn was first described in the medical literature 1609, when it was diagnosed in one French housewife. In 1932 Diamond and colleagues described the mutual relationship of fetal hydrops, jaundice, anemia and erythoblastosis, which was later called fetal erytroblastosis. Hemolytic disease of the newborn (HDN) in the strict sense is considered disease whose basis is accelerated immune destruction of fetal/child erythrocytes that are bound to IgG antibodies of maternal origin. These antibodies are directed against antigens of father’s origin, which are present in the fetal/children’s erythrocytes and that the mother’s immune system recognizes them as foreign antigens. GOAL: The goal is that in the period from January 1(st) 2011 to October 23(st) 2013 determine the frequency of ABO and Rh D incompatibilities in our sample of pregnant women/mothers, and to underscore the importance of regular check of ABO Rh D negative pregnant women and application specific Rh D protection. MATERIAL AND METHODS: In the General Hospital “Prim. Dr. Abdulah Nakas” in Sarajevo by retrospective study are followed several relevant variables. Immune alloantibodies were detected in vivo by indirect Coombs test (ICT) with serum mother and O test erythrocytes, by direct Coombs test (DCT) with erythrocytes of a newborn. RESULTS: The total number of births ABO Rh D negative was 596 (14%) and ABO Rh D positive mothers 4261 (86%). Of the total number of Rh D negative mothers there was A Rh D: negative mothers 42%; O Rh D negative 33%; B Rh D: negative 17% and AB Rh D: negative 8%. Most of immune antibodies appear in mothers with O Rh D: negative blood type. The emergence of immune antibodies in the Rh D negative mothers was 1%, the appearance of ABO incompatibilities amounted to 2.3% of our sample. CONCLUSION: In order to reduce the occurrence of alloimmunization of the mother to erythrocyte antigens of the newborn that can lead to major complications in subsequent pregnancies of Rh D: negative mothers and HDN constant monitoring in order to prevent them is necessary. Prevention is essential because once immunized mother will remain immunized for life.